Citizenship-Behaviour and Workplace-Withdrawal: Distinguishing Between the Organization and Job-Based Turnover Intentions in Nurses - Shah, Syed Imad; Shahjehan, Asad; Ali, Muhammad Daud; Manzoor, Humera (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the relationship of nurses’ organizational citizenship behaviour with their organization-based and job-based turnover intentions. As no prior research has explored the relationship of nurses’ organizational citizenship behaviour with intentions to leave the organizations and current job as separate behavioural outcomes, therefore, this research serves to fill an important research gap. This study is carried on the faculty members of nursing education institutes in Pakistan. 124 full-time and part-time faculty members participated in the survey. Among the four dimensions of OCB sportsmanship, civic virtue, and helping were found to be highly significant predictors of organization-based and job-based turnover intentions. Interestingly the relationship between Altruism and organization-based turnover intentions was found to be insignificant. This study improves our understanding about the relationship between nurses’ organizational citizenship behaviour and organization and job-based turnover intentions. It makes a contribution to the extant literature as it adds empirical findings to the existing body of knowledge. Furthermore, this study provides us with exciting practical implication especially in the area of employee retention in general and nurse retention in specific. The results of this study can help managers to understand turnover intentions and its OCB precursors.Key words--Organizational citizenship behaviour, organization based turnover intentions, Job-based turnover intentions